If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -3(6) = 0 Multiply -3 * 6 6 + -18 = 0 Combine like terms: 6 + -18 = -12 -12 = 0 Solving -12 = 0 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| w-6-12=-8 | | 3a+7b=23 | | 1x=7 | | 4t=56 | | 2(-3)+[5(-5)]= | | m=-7(6-5) | | =-7(6-5) | | x^2-20x-9900=0 | | (9x-6)+3=(14x+28) | | (7-1)(5-8)= | | -20+3t=65 | | -16x^2-y+1156=0 | | -16x^2-x+1156=0 | | -20+3t=-65 | | 4p/3-p/4=6+5p/6 | | (10-3x)=(50x) | | x-(2x-1)=3 | | 4a+8c=16 | | x^2-2.6x-3.12=0 | | 6a+12q=18 | | x/7+x/6=39 | | x-38=24 | | x^2+x-272=0 | | 130=5(x-60)+55 | | -9(-5d-12)-9d=-18d | | 2y+4=3y+12 | | 6(-17g+4)=20-17g+4 | | 3x-24=2x | | 12x=81 | | 64-y=36 | | 7m-3m+1= | | -7=-(x+8) |